Ecology of Anopheles dthali Patton in Bandar Abbas District, Hormozgan Province, Southern Iran - H Vatandoost; M Shahi; AA Hanafi-Bojd; MR Abai; MA Oshaghi; F Rafii (Tehran University of Medical Sciences, 2007)
Ecology of Anopheles dthali was studied in Bandar Abbas County, where there is indigenous malaria. Anopheles dthali plays as a secondary malaria vector in the region. It is active throughout the year in mountainous area with two peaks of activity, whereas in coastal area it has one peak. There is no report of hibernation or aestivation for this species in the re¬gion. Precipitin tests on specimens from different parts showed that 15.6-20.8% were positive for human blood. This species usually rests outdoors. It has different larval habitats. Insecticides susceptibility tests on adult females exhibited susceptibil¬ity to all insecticides recommended by WHO. LT50 for the currently used insecticide, lambda-cyhalothrin, is measured less than one minute. The irritability tests to pyrethroid insecticides, showed that permethrin and lambda-cyhalothrin had more irritancy compared to deltamethrin and cyfluthrin. Larval bioassay using malathion, chlorpyrifos, temephos and fenithrothion did not show any sing of resistance to these larvicides at the diagnostic dose. It is recommended that all the decision makers should consider the results of our study for any vector control measures in the region.